First report of anthracnose caused by Colletotrichum gloeosporioides on Brachychiton populneus in Argentina - Colombo, Denis Nahuel; Comerio, Ricardo Mario (Wiley, 2024)
Brachychiton populneus (brachychiton, kurrajong) is widely grown as a street tree in La Pampa, Argentina. During 2020, 95 urban trees were surveyed for foliar disease. Symptoms, not previously recorded, were detected on leaves of B populneus in the northern region of the province. These began as small, circular to irregular, brown, necrotic lesions on both sides of the leaf blade, turning black with a grey central area as they aged, arranged randomly on the leaf surface.